ROLE OF ANTIOXIDANTS IN METABOLISM: A BRIEF REVIEW - GOPAL KRISHNA SAHU (International Journal of Pharma and Bio Sciences, 2016)
Reactive oxygen species (ROS) are produced as a normal product of cellular metabolism. Various environmental stresses lead to excessive production of ROS causing progressive oxidative damage and ultimately cell death. The very common ROS are hydroxyl radicals (.OH), superoxide anion radicals (O2._), hydrogen peroxide (H2O2), singlet oxygen (1O2), hypochlorite radical (ClO-), nitric oxide (NO) radical and many types of lipid peroxides. These radicals have some physiological functions at lower concentrations but at higher concentrations impart very deleterious effects on biomolecules such as lipids, proteins and nucleic acids. To prevent the damaging effects of these harmful oxidants, aerobic organisms have evolved a highly structured system of compounds known as antioxidants. Some of the low molecular weight non-enzymatic antioxidants include ascorbate, alpha-tochopherol, glutathione, carotenoids and flavonoids etc. Whereas catalase, superoxide dismutase, glutathione reeducate and peroxidases are the important types of enzymatic antioxidants induced in response to oxidative stress both in plants and animals. A general account of some important enzymatic and non-enzymatic antioxidants has been reviewed in this paper.